ON THE PROBLEM OF RELATION BETWEENTHE SYSTEM-FUNCTIONAL AND THE FIVE-FACTOR MODELS OF PERSONALITY TRAITS - A I Krupnov; I A Novikova; A A Vorobyeva (Peoples' Friendship University of Russia (RUDN University), 2016)
The article compares some problems of the person and the personality study in Russian and foreign (primarily US) psychology. The authors describe the phenomenology of the personality as it is perceived and described in a textbook published by the American Psychological Association in 2015. The structure of the Five-Factor model ("Big Five") as one of the main approaches to the study of personality in foreign psychology and the System-Functional Approach to the personality traits analysis, which embodies many Russian psychology traditions, are briefly presented in the paper. The main results of the comparative study of the curiosity and persistence as system-functional personality traits and the "Big Five" factors (neuroticism, extraversion, openness, agreeableness, consciousness) are described and analyzed. The sample includes 207 first and second-year university students of Linguistics department. The Big Five factors were measured with the Russian NEO Five-Factor Inventory adaptation by S.Biryukov and M.Bodunov, curiosity and persistence as system-functional personality traits were measured with the paper-and-pencil test developed by A.I. Krupnov. The Spearman correlation analysis and factor analysis were used for statistical analysis. The study shows that there are stable correlations between Persistence as a conative personality trait studied within the System-Functional Approach framework and Consciousness as a Five-Factor Model trait, and Curiosity as a cognitive trait and Openness (within the same respective frameworks). Persistence shows closer associations with the factors of the Big Five model than Curiosity. Extraversion and Neuroticism as individual-personal factors characterize a measure of a person's activeness in the implementation of their personality traits and difficulties in these traits implementation, respectively.